Platform socialism : how to reclaim our digital future from big tech - Muldoon, James, author. 3505 1985- (London : Pluto Press, 2022)
"Powerful tech companies now own the digital infrastructure of twenty-first-century social and economic life. Masquerading as global community builders, these companies have developed sophisticated new techniques for extracting wealth from their users. James Muldoon shows how grassroots communities and transnational social movements can take back control from Big Tech. He reframes the technology debate and proposes a host of new ideas, from the local to the international, for how we can reclaim the emancipatory possibilites of digital platforms."--From back cover. Includes bibliographical references (pages 157-178) and index. All the word's a platform -- Monetising community -- Community-washing big tech -- Private power and public infrastructure -- Guild socialism for the digital economy -- Building civic platforms -- Global digital services -- Recoding our digital future -- Postscript: 2042. "Powerful tech companies now own the digital infrastructure of twenty-first-century social and economic life. Masquerading as global community builders, these companies have developed sophisticated new techniques for extracting wealth from their users. James Muldoon shows how grassroots communities and transnational social movements can take back control from Big Tech. He reframes the technology debate and proposes a host of new ideas, from the local to the international, for how we can reclaim the emancipatory possibilites of digital platforms."--From back cover.